How Inclusive is “Inclusive Development” in India? Challenges and Prospects of Indian Youth Labour Market - Bisht, Nitin; Pattanaik, Falguni (International Business Education Journal, 2021)
This study investigates the degree of inclusiveness of youth in the Indian labour market concerning Goal 4 and Goal 8 of the Sustainable Development Goals-2030. For this purpose, the study engages logistic regression by considering the 50th (1993/94), 55th (1999/00), 61st (2004/05) and 68th (2011/12) rounds of (un)employment surveys of NSSO. The empirical results reflect the high exclusion of youth in the Indian labour market, especially the female youth. By highlighting labour market exclusion as a challenge to economic development, the study further explores the intensity of risk factors affecting youth to remain excluded from the labour market. The findings divulge that gender remains a significant contributor to exclusion, often restricting access to employment. However, youth from low income, minorities, certain castes or religious groups are in many cases, even more, excluded from economic development. The implications of this study contribute by identifying the risk factors of youth transition in the Indian labour market. The findings add significant value to the limited youth labour market studies in India and advocates on the policy front to create better labour market opportunities to re-integrate NEET youth into a gainful activity. Therefore, a holistic approach within the broader context of macro (government and society), meso (household) and micro (individual) development need to be considered in order to make ‘youth’ more inclusive in the economic development of the country.